2003
DOI: 10.1038/sj.gene.6363983
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of Th1–Th2 cytokine genes in an AIDS cohort: identification of IL4 and IL10 haplotypes associated with the disease progression

Abstract: Polymorphisms of Th1-Th2 cytokine genes have previously been implicated in the rate of progression to AIDS in seropositive patients. To evaluate further the impact of these genes in the development of AIDS, we have performed an extensive genetic analysis of IL2, IL4, IL6, IL10, IL12p35 and p40, IL13 and IFNg. The coding regions and promoters of these genes were sequenced in a Caucasian cohort of 337 HIV-1 seropositive extreme patients (the GRIV cohort) consisting of patients with slow progression and rapid pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 50 publications
0
47
1
1
Order By: Relevance
“…[24][25][26][27] Molecular genetic epidemiological studies have identified polymorphisms in more than 20 human genes, including several chemokines and their receptors, that are associated with HIV-1 infection and/or AIDS disease pathogenesis. [28][29][30][31][32][33][34][35][36][37][38][39][40] Given the importance of SDF-1 in various metabolic and developmental activities, we examined the allele frequencies and haplotype structure of nine SNPs in and around the SDF-1 gene. In addition, given the important role played by SDF-1 and CXCR4 in HIV-1/AIDS, we looked for the influence of genetic variation in these SNPs and haplotypes on disease in over 3000 subjects enrolled in five USA-based natural history HIV-1/AIDS cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Molecular genetic epidemiological studies have identified polymorphisms in more than 20 human genes, including several chemokines and their receptors, that are associated with HIV-1 infection and/or AIDS disease pathogenesis. [28][29][30][31][32][33][34][35][36][37][38][39][40] Given the importance of SDF-1 in various metabolic and developmental activities, we examined the allele frequencies and haplotype structure of nine SNPs in and around the SDF-1 gene. In addition, given the important role played by SDF-1 and CXCR4 in HIV-1/AIDS, we looked for the influence of genetic variation in these SNPs and haplotypes on disease in over 3000 subjects enrolled in five USA-based natural history HIV-1/AIDS cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…It has generally been accepted that a Th1/Th2 imbalance underlies various immune diseases. In HIV-infected patients and LP-BM5-infected mice, T-cell proliferation and Th1 cytokine (IL-2 and IFN-␥) production have been reported to decline, while Th2 cytokine (IL-4, IL-5, IL-6, and IL-10) and immunoglobulin production increase (4,5,10,12,26,34,45,49,57).…”
Section: Vol 80 2006 Cd4 T Cells In the Pathogenesis Of Murine Aidsmentioning
confidence: 99%
“…Th1 cells are involved in the pathogenesis of several organ-specific autoimmune disorders. In contrast, allergen-specific Th2 responses may be critical for atopic disorders in genetically susceptible individuals, and skewing to a Th2 response in certain infections diseases, such as leishmaniasis, leprosy, and others, results in a lack of clearance of the causative microbe and consequently in enhanced microbial and/or immunological pathology (4,34,45,57).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The IL-10 haplotypes or genotypes defined as low IL-10 producers have been associated with HCV clearance [9][10][11] and the outcome of other infectious agents, including progression of HIV infection. 12 The complex influences of genetic and environmental factors are apparent in ethnic variations in the sequelae of HCV infection. African Americans have a higher prevalence of acute and chronic HCV infection than Caucasians (CAs).…”
Section: H Epatitis C Virus (Hcv) Infects Approximatelymentioning
confidence: 99%